Daniel-Franc̦ois-Esprit Auber's Les Chaperons blancs - Letellier, Robert Ignatius (Cambridge Scholars Publishing, 2019)
Daniel-François-Esprit Auber (1782-1871), the most amiable French composer of the nineteenth century, came to his abilities late in life. After a stalled commercial career, he studied with Cherubini. His first works were not a success, but La Bergère Châteleine (1820), written at the age of 38, established him as an operatic composer. He then met the librettist Eugène Scribe (1791-1861), with whom he developed a working partnership, one of the most successful in musical history, that lasted until Scribe's death. After Le Maçon (1825) and La Muette de Portici (1828), Auber's life was filled wit.